2022
DOI: 10.1161/circulationaha.121.058457
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Acute Myocarditis and the Overlap With Inherited Cardiomyopathy

Abstract: Background: Acute myocarditis is an inflammatory condition that may herald the onset of dilated cardiomyopathy (DCM) or arrhythmogenic cardiomyopathy (ACM). We investigated the frequency and clinical consequences of DCM and ACM genetic variants in a population-based cohort of patients with acute myocarditis. Methods: This was a population-based cohort of 336 consecutive patients with acute myocarditis enrolled in London and Maastricht. All participants underwent targeted DNA sequencing for well-chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 53 publications
2
58
0
2
Order By: Relevance
“…Patients with dilated cardiomyopathy and a pathogenic TTN variant can also develop fulminant myocarditis as an initial presentation, as described in a case report in the Journal [24] . This finding was further confirmed by a large cohort that identified pathogenic TTN truncating variants in 7% of all patients presenting with myocarditis complicated by left ventricular systolic dysfunction [19] .…”
Section: Myocarditismentioning
confidence: 59%
See 1 more Smart Citation
“…Patients with dilated cardiomyopathy and a pathogenic TTN variant can also develop fulminant myocarditis as an initial presentation, as described in a case report in the Journal [24] . This finding was further confirmed by a large cohort that identified pathogenic TTN truncating variants in 7% of all patients presenting with myocarditis complicated by left ventricular systolic dysfunction [19] .…”
Section: Myocarditismentioning
confidence: 59%
“…Perhaps the most relevant news in the field of myocarditis are that we could collect reports related to myocarditis with a clear genetic background [18] , [19] , myocarditis associated with COVID-19 infection [20] , [21] , and myocarditis in conjunction with COVID-19 vaccination [22] , [23] .…”
Section: Myocarditismentioning
confidence: 99%
“…Patients with a genetic predisposition may remain phenotypically silent until an environmental trigger occurs. The TTN tv clinical phenotype is also particularly susceptible to environmental factors, which can favor the onset of the disease [ 45 , 46 , 47 ]. At first sight, the present case could be classified as an acquired form of DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies employing highly advanced but clinical practice-ready genetic diagnostics [4,[22][23][24] have revealed significant direct impact of myocardial inflammation upon the induction of life-threatening arrhythmias. These studies investigated patients with well-defined genetic anomalies identified by large-scale mutation scanning.…”
Section: New Figure 2 Cellular Receptors and Signaling Pathways Linki...mentioning
confidence: 99%